(untitled) (London Journal of Research In Management & Business, 2025)
This article aims to evaluate the impact of the PlaytechEdu platform on educational indicators in the municipality of So Miguel dos Campos - Alagoas, demonstrating how this platform positively influences data monitoring and demonstrating the importance of these technologies in achieving improvements in municipal education. The research will demonstrate, based on descriptions of the features of the PlaytechEdu platform, how it has been implemented in the municipality of So Miguel dos Campos - Alagoas, based on a data analysis and comparison with municipal educational indicators before and after the implementation of the platform. Finally, it will seek to discuss the role of startups and govetechs in public management innovation, and their influence on the improvement of public services. The research uses a mixed research line, graphically demonstrating the improvement resulting from the implementations, based on a documentary analysis of reports, spreadsheets and data provided by the education department of the municipality of So Miguel dos Campos. Thus, the research seeks to show how the implementation of PlaytechEdu is a significant factor in the search for educational quality in the municipality of So Miguel dos Campos, corroborating the digital technological potential in educational transformation and improvement of local results.